Distribution Nudibranch and Carnivorous Fish in The North Bali Sea - Wirawan, Kadek Fendi; Munasik, Munasik; Suprijanto, Jusup; Pravitasari, Anggi Karina (Universitas Diponegoro, 2024)
The presence or absence of certain types of carnivorous coralfish in a coral reef ecosystem accurately indicates the health of a coral reef ecosystem and the organisms associated with it; one of them is the nudibranch. This research aims to determine whether the presence of carnivorous fish in coral reef ecosystems affects the quality of the nudibranch life cycle and the distribution size in terms of predation. Nine carnivorous fish species were found at the three research stations, the largest group being triggerfish and grouper found in Lovina Reef and Menjangan island. Observed from the size distribution of nudibranchs, the presence of nudibranchs in the three research locations shows sizes ranging from small to large, namely from the Phyllididae nudibranch group. The dead body of the nudibranch was found in Tulamben reef, but it could not be confirmed whether the nudibranch was preyed by carnivorous fish. Carnivorous fish are not predators and do not affect the life cycle of nudibranchs observed from the complete size distribution of nudibranchs from small to large. Nudibranch predators cannot digest nudibranch bodies because their bodies are venomous; they use them as self-defense against the predators. Nudibranchia are not always found when preyed on by fish.